2020
DOI: 10.21037/apm-20-1012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of homogeneous and heterogeneous risk factors on the incidence and prognosis of brain metastases in patients with hepatocellular carcinoma

Abstract: Background: This study aimed to identify the incidence, risk factors, and survival outcome associated with brain metastases (BM) in hepatocellular carcinoma (HCC) patients using a large-scale population-based cancer registry database.Methods: Between 2010 and 2016, patients with BM from HCC were included using the Surveillance, Epidemiology, and End Results (SEER) program. The risk and prognostic factors for BM were recognized by multivariate logistic and Cox regression model analysis. The overall survival (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…HCC has a poor prognosis, with a 5-year overall survival of 18%, especially for patients with brain metastases, with a median OS of 1.2–2.4 months [ 3 , 4 ] and a very high mortality rate. However, due to the low incidence of HCC with BMS, overall accounting for 0.2%–2.2% [ 5 ], poor prognosis, and lack of specific symptoms of early BMS, clinicians rarely pay attention to HCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC has a poor prognosis, with a 5-year overall survival of 18%, especially for patients with brain metastases, with a median OS of 1.2–2.4 months [ 3 , 4 ] and a very high mortality rate. However, due to the low incidence of HCC with BMS, overall accounting for 0.2%–2.2% [ 5 ], poor prognosis, and lack of specific symptoms of early BMS, clinicians rarely pay attention to HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulty of early diagnosis of BMS, and HCC patients often spread to other extrahepatic sites before BMS, the indications for the treatment of HCC patients with BMS are a major challenge for surgeons. Early diagnosis of BMS, radiotherapy combined with molecular targeted therapy and immunotherapy, can bring certain treatment opportunities for advanced HCC patients with BMS [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al 16 noted that gender, grade, N stage, tumor size, and intrahepatic metastasis were significantly associated with lung metastasis in ICC. Lin et al 17 found that age, grade, surgery, radiotherapy, chemotherapy, bone metastasis, and lung metastasis were independently positively associated with BM in the HCC cohort. These factors also reflect the invasion ability of the primary tumor to varying degrees, thus suggesting that these indicators can be used as risk factors for extrahepatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Non-White race and advanced stage were associated with poor prognosis. Many studies have found that race could serve as a prognostic factor for various cancers such as hepatocellular carcinoma, [16] lymphoma, [17][18][19] and breast cancer. [20] Lower treatment rates and delayed onset of treatment may account for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%